Answer:
use -9 to multiply the first equation
use -4 to multiply the second equation.
Step-by-step explanation:
5x-4y=28.....eqn (1)×-9
3x-9y=30....eqn(2)×-4
-45x+36y=-252
-(-12x+36y=-120)
therefore, -33x÷33 =-132÷-33
x=4.
substitute (x=4) in any of the equation. I'm just going to use eqn 1.
5x-4y=28
5(4)-4y=28
20-4y=28
-4y =28-20
-4y÷-4 = 8÷-4
y=-2
so, x=4, y=-2
Note: for proof of answers substitute the answers for x and y and see if you have the same result...e.g
5(4)-4(-2)=28.
B: 3 and 4 because they both do not have an = sign
In trigonometry, we start from the point (1,0), so this is the 0-degree point. Then, we start rotating counter clockwise along the unit circle.
Note that rotating 180 or -180 degrees is actually the same, because you travel half the circumference clockwise or counter clockwise. In both cases, you start from the rightmost point of the circle, (1,0), and arrive at the leftmost point, (-1,0).
Now, for every point (x,y) on the unit circle, given by a certain angle , we have
So, in this case, the angle of -180 is associated with the point (-1,0), and thus we have
Answer:1/10
Step-by-step explanation:
Answer:
GCF = 4
Step-by-step explanation:
The factors of 8 are: 1, 2, 4, 8
The factors of 12 are: 1, 2, 3, 4, 6, 12
The greatest common factor is 4.
I hope this helps :).